105 Provider perceptions on the management of lupus during pregnancy: barriers to improved care. (April 2019) - Clowse, Megan EB; Revels, Jessica; Eudy, Amanda M; Schmidler-Sanders, Gillian; Neil, Laura; Criscione-Schreiber, Lisa G
Abstract : Background: More than half of pregnancies in women with systemic lupus erythematosus (lupus) result in adverse outcomes for both mother and fetus. As demonstrated in the PROMISSE study, pregnancies managed by experts can have outcomes similar to the general population. However, many women with lupus do not receive this level of care and suffer complications at higher rates. We sought to identify aspects of current community rheumatologic care that could be improved to decrease the frequency of poor lupus pregnancy outcomes. Methods: Focus groups with clinical rheumatologists were held at state rheumatology conferences in North Carolina, South Carolina, Virginia, and Northern California. The interview guide was based on the PRECEDE/PROCEED framework, seeking factors that predisposed, reinforced, and enabled physician practice patterns. Focus groups were recorded, transcribed, and coded to identify the elements of this framework. A group of women with lupus on their reproductive journey contributed to our understanding of the dilemmas and care provided. Results: In 6 focus groups including 36 rheumatologists (37% male), the key dilemma in lupus pregnancy was reported to be medically ill-timed pregnancies. We identified four modifiable barriers to effective pregnancy planning: 1.) physician/patient communication about contraceptive use was often directive, which is ill-suited to the sensitive discussion; 2.) some rheumatologists have a knowledge gap, with only 37% identifying mycophenolate mofetil as a major teratogen and most greatly over-estimating the efficacy of Depo-provera®; 3.) local rheumatologists and OB/GYN frequently did not communicate, leading to varying treatment plans and confusion for patients; and 4.) pregnancy planning conversations were derailed by limited patient-trust and physician-empathy about a young womans desire to be a mother. Conclusions: While we hope that the coming inaugural ACR Reproductive Health Guidelines will improve pregnancy management and outcomes for women with SLE, prior research demonstrates that simple guideline publication does little to influence care. We have identified several important, modifiable factors that, if addressed, may allow the guidelines to have a stronger impact on pregnancy success. We have built HOP-STEP (Healthy Outcomes in Pregnancy in women with SLE Through Educating Providers), an in-person and online program, to enable open and honest conversations about pregnancy planning and management between rheumatologists and women with lupus (www.LupusPregnancy.org). Funding Source(s): AHRQ: K18HS023443